Relationship between the degree of obesity and oral glucose tolerance in primary obese adolescents - Argo Pribadi; Dedi Subardja; Diet F. Rustama; Ryadi Fadil (Indonesian Pediatric Society, 2002)
Background Obesity has long been recognized as a risk factor for a variety of adverse health consequences. Obese adolescents tend to have a decrease in sensitivity to insulin resulted in elevated plasma glucose level. The oral glucose tolerance test has often been used to evaluate this insulin resistance. The aim of this studyObjective To find out the relationship between the degree of obesity (according various classification) and the ability to tolerate oral glucose load in adolescents with primary obesity.Methods Subjects of this cross-sectional study consisted of 75 adolescents aged between 12 and 15 years. Obesity status was detennined according to the weight for height (W-H), body mass index (BMI), triceps skin folds thickness (TST) and sub scapular skin folds thickness (SST) classifications. All subjects underwent oral glucose tolerance test. The plasma glucose level was measured while fasting and two hours after taking 1.75 gram glucose per kilogram of body weight (maximum 75 gram). Impaired glucose tolerance was defined as a fasting glucose level s.126 and two-hour plasma glucose 3 140 mg/dL but < 200 mg/dL.Results There was a significant difference in two-hour plasma glucose level between the mild and moderate obese group based on W-H classification (P=0.02), also between the non obese and the obese group based on BMI classification (P=0.02). The Pearson's correlation of two-hour plasma glucose level with W-H and BMI parameters showed a significant correlation (r = 0.316; P=0.005 and r = 0.268; P=0.018). There were two adolescent girls who showed impaired glucose tolerance.Conclusion Although impaired glucose tolerance found only in a few obese adolescents, decreased ability to tolerate oral glucose load was found in subjects studied and correlated well with the degree of obesity.